Chemical properties and classification of soils cultivated with banana in the Caribbean lowlands of Costa Rica - Arias, Fulvio (2009)
Soils from 11 watersheds planted with banana in the aluvial valleys of the Caribbean zone of Costa Rica were chemically characterized and classified. Two major soil areaswere identified based on their morphological and chemical properties and taxo-nomic criteria. One of the areas consisted mainly of Inceptisols formed from fluvio volcanic materials with andic properties (Andic Eutrudepts, Aquandic Endoaquepts), dystric Inceptisols (Flu-ventic Dystrudepts) and Andisols (Typic Haplu-dands), most with good drainage, medium textu-res (sandy loam, loam, silty loam), sum of bases 10 to 19 cmol.l-1, CEC 13 to 28 cmol.l–1 and clays with permanent charge. The adjacent zone consisted mainly of Inceptisols formed from alu-vial sedimentary materials deposited by frequent river floods (Fluventic Endoaquepts, Dystric Fluventic Eutrudepts, Fluvaquentic Eutrudepts, Fluvaquentic Endoaquepts), with a sum of bases 18 to 46 cmol.l–1, CEC 19 to 46 cmol.l–1, without Andic properties, textures fine to medium (clay loam, silty clay loam, clay, silty clay) and in some case with poor drainage (Endoaquepts, Epiaquepts, Fluvaquentic). Geographically, the 2 zones were separated by the watersheds of Vueltas-Silencio Parismina Rivers; the northwest area is highly influenced by volcanic ash deposits and has its medium fertility characteristics, while the southeast area is not influenced by volcanic ejecta and has high fertility characteristics.